EFFECTS OF WOOD ASH ON GEOTECHNICAL PROPERTIES OF LATERITIC SOILS - Tobi, Aboluwarin; S, Ologun; W.E, Esuabanga; G.C, Osuorji (International Journal of Engineering Technologies and Management Research, 2022)
Biochar can be derived from pyrolysis of agricultural waste, wood waste (saw dust), logging residues and other biological waste. Biochar can be use to improve the quality of construction and engineering materials. The study deals with the effect of biochar (wood ash) on geotechnical properties of lateritic soils, and it is to investigate the effect of wood ash on the geotechnical properties of lateritic soils. For these purpose, soil samples that were gotten from borrow pit were made use of and blended with available biochar which is used as a stabilizing agent. This was done at different percentages which include (0%, 3%,5%, 10%,15% and 20%,). The biochar was sieved with 125 micrometer sieve and were after blended with the soil samples. The compaction test, consistency limit test, the unconfined compressive strength test were carried out on the samples. It was discovered that the OMC of the blended samples increases as the percentages of the biochar that was used to blend the samples increases, also the MDD on the contrary decreases. The unconfined compressive strength test were conducted on all the samples (0%,3%,5%,10%,15% and 20%). It was also discovered that the compressive strength of soil samples increases with increase in the addition of biochar of the samples having its peak at 10%. Then reduction in compressive strength was experienced in between 11% to 20% addition of biochar to the soil sample. Conclusively, the results show that biochar can be use as stabilizing material when added to lateritic soil samples. But more addition of it at a particular stage may lead to the reduction in the compressive strength of the sample in which the sample may be weak and brittle. The size of the biochar if not properly crushed and sieved may not yield a desired result.